2003
DOI: 10.1046/j.1538-7836.2003.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of T-cell epitopes in clotting factor IX and lack of tolerance in inbred mice

Abstract: Summary. Immune responses to the factor IX protein pose problems for hemophilia B patients who develop antibodies against factor IX and for potential future treatment with gene therapy. To better define the response to human factor IX, we analyzed T-cell responses to human factor IX in factor IX knockout mice on BALB/c and C57BL/6 (B6) backgrounds, both strains having CD4þ T cells that proliferate in response to human factor IX. Surprisingly, wild-type mice have similar factor IX-recognizing CD4þ T cells. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…A representative example is shown in Figure 1A. Splenocytes from hemophilia B mice on a C57BL/6 background proliferated upon stimulation with peptide 2A-58 (NKYNNHDIALLELDEPLV-LNS), which is consistent with data published by Greenwood et al, 25 who identified immunodominant CD4 ϩ T-cell epitopes for hF.IX in C57BL/6 and BALB/c mice. Combined data from our study and the Greenwood et al 25 study show that peptides containing immunodominant CD4 ϩ T-cell epitopes in C57BL/6 (H-2 b ), BALB/c (H-2 d ), and C3H/HeJ (H-2 k ) mice are clustered in a sequence of hF.IX that is part of the catalytic domain of the serine protease ( Figure 1B).…”
Section: Mapping Of the Immunodominant T-cell Epitope In C3h/hej Micesupporting
confidence: 88%
“…A representative example is shown in Figure 1A. Splenocytes from hemophilia B mice on a C57BL/6 background proliferated upon stimulation with peptide 2A-58 (NKYNNHDIALLELDEPLV-LNS), which is consistent with data published by Greenwood et al, 25 who identified immunodominant CD4 ϩ T-cell epitopes for hF.IX in C57BL/6 and BALB/c mice. Combined data from our study and the Greenwood et al 25 study show that peptides containing immunodominant CD4 ϩ T-cell epitopes in C57BL/6 (H-2 b ), BALB/c (H-2 d ), and C3H/HeJ (H-2 k ) mice are clustered in a sequence of hF.IX that is part of the catalytic domain of the serine protease ( Figure 1B).…”
Section: Mapping Of the Immunodominant T-cell Epitope In C3h/hej Micesupporting
confidence: 88%
“…44 These 3 residues are located outside the F.IX regions recently recognized containing T-cell epitopes in mice of distinct strains immunized to human F.IX. 45 Together these data suggested that it is unlikely that these changes in F.IX amino acid are located in highly immunogenic regions. Since all 3 residues that were substituted in these studies are conserved in the canine F.IX, further experiments in outbred large-animal models of hemophilia B are warranted to determine the risk of antibody to each F.IX variant.…”
Section: Discussionmentioning
confidence: 91%
“…Second, when injected into the liver parenchyma, PEPs are able to engraft robustly and restore wild-type hepatocellular function in F-IX-deficient mice. F-IX-deficient mice (18,19) have a phenotype that is similar to hemophilia B in humans, characterized by a severe bleeding diathesis caused by absence of F-IX protein (20,21). F-IX has a short half-life requiring continuous replacement, and, consequently, any substantial production of mouse F-IX in the deficient mice indicates hepatocyte function derived from the engrafted PEPs.…”
Section: Discussionmentioning
confidence: 99%